1998
DOI: 10.1074/jbc.273.46.30427
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced Diabetes Activates an Osteogenic Gene Regulatory Program in the Aortas of Low Density Lipoprotein Receptor-deficient Mice

Abstract: Vascular calcification is common in people with diabetes and its presence predicts premature mortality. To clarify the underlying mechanisms, we used low density lipoprotein receptor-deficient (LDLR ؊/؊) mice to study vascular calcification in the ascending aorta. LDLR ؊/؊ mice on a chow diet did not develop obesity, diabetes, atheroma, or vascular calcification. In contrast, LDLR ؊/؊ mice on high fat diets containing cholesterol developed obesity, severe hyperlipidemia, hyperinsulinemic diabetes, and aortic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
231
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 34 publications
13
231
0
1
Order By: Relevance
“…Advanced calcific lesions can develop woven bone and even commence hematopoiesis. This remodeling of the vasculature can extend to the point of acquiring some functional characteristics of bone, offering the perspective that VC occurs in a manner similar to bone development 48, 60, 61, 62. Briefly, osteogenesis involves formation of mesenchymal cell condensations, which differentiate into bone‐forming cells for intramembranous or endochondral ossification 63, 64.…”
Section: Vascular Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced calcific lesions can develop woven bone and even commence hematopoiesis. This remodeling of the vasculature can extend to the point of acquiring some functional characteristics of bone, offering the perspective that VC occurs in a manner similar to bone development 48, 60, 61, 62. Briefly, osteogenesis involves formation of mesenchymal cell condensations, which differentiate into bone‐forming cells for intramembranous or endochondral ossification 63, 64.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…The latter has been demonstrated in atherosclerotic lesions, particularly in vascular myofibroblasts and endothelium 93. BMP2 expression is activated by pathogenic stimuli, such as tumor necrosis factor‐α,94 oxidized lipids,94 and hyperglycemia95, 96 More important, BMP2 has been demonstrated to regulate osteogenic programs contributing to VC 55, 62. One of the main ways in which BMP2 regulates osteogenic gene expression programs is through the induction of transcription factor Msx2, which controls craniofacial mineralization 97.…”
Section: Implication Of Wnt Signaling In Atherosclerotic Calcificationmentioning
confidence: 99%
“…This HFD was previously shown by Towler and colleagues to increase atherogenic lipoproteins in this mouse model. (30) Realtime RT-qPCR of the calvarial tissues showed that the HFD significantly reduced expression of bone-formation markers, PTH receptor, core binding factor a1 (Cbfa-1), bone sialoprotein, and osteocalcin ( Fig. 2A).…”
Section: Effect Of the Hfd On Gene Expressionmentioning
confidence: 99%
“…Demer first demonstrated BMP2 expression as a feature of atherosclerotic calcification (8). Following these seminal observations, others detailed the temporospatial expression of BMP2-regulated intramembranous and endochondral gene expression programs in calcific vasculopathy (13,14). Thus, in addition to being key inhibitors of tissue mineralization (15)(16)(17)(18), osteogenic programs actively contribute to vascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…In response to high-fat diets, male LDLR -/-mice develop diabetes and dyslipidemia (14). In this model of disease initiation, in situ hybridization studies demonstrated that the pattern of Msx2 expression in cardiac valves and adventitial myofibroblasts overlaps the expression pattern of Acta2 (i.e., VSMC α-actin) (14). Msx2 is a BMP2-inducible transcription factor that controls craniofacial mineralization (20).…”
Section: Introductionmentioning
confidence: 99%